Teacher Readiness in Handling Inclusive Students in Elementary School - Meri Septiana Putri; Siti Quratul Ain (Universitas Pendidikan Ganesha, 2022)
Inclusive schools often experience difficulties and obstacles in providing services to inclusive students. This study analyzes the forms and factors influencing teacher readiness to handle inclusive students in elementary schools. This research uses a qualitative research type with a descriptive approach. The implementation of this research starts from the design, research, implementation, data analysis and making research reports. Data collection techniques used in this study include interviews, observation, and documentation. The subjects and objects of this research were the principal, 2 teachers, one first grade student, and one second grade student. The results of interviews and observations clearly show that teachers are not ready to handle inclusive students due to the lack of knowledge and concern of teachers for inclusive students. Lack of class teacher acceptance of inclusive students includes internal factors in the form of physical, mental and emotional conditions, motivation to improve experience and maturity. The negative attitude factors of teachers towards inclusive students include internal in the form of emotional conditions and social competence. Teachers' lack of knowledge and understanding about dealing with inclusive students includes external factors in the form of skills, knowledge, intelligence, and professional competence.